(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2025)
This article examines the motivational story as a special speech genre that functions at the intersection of communication, pedagogy and culture. The author analyzes the structural features of motivational stories, their pragmatic focus and semi-cultural nature. The study is based on the approaches of discourse analysis and linguacultural studies, emphasizing the role of motivational stories in the formation of behavioral models and value attitudes of the individual.